DAMPAK KEBIJAKAN HARGA BERAS DAN LUAS AREAL IRIGASI TERHADAP PENGENTASAN KEMISKINAN DI INDONESIA - Dudi Septiadi; Harianto Harianto; Suharno Suharno (Jurnal Agribisnis Indonesia, 2016)
Poverty is one of the major problems in Indonesia is unresolved. Rice is the main food commodities that affect the welfare of million people in Indonesia. Rice is a major source of calories most of the Indonesian people. The objective of this study was to analyze the impact of rice policy on poverty in Indonesia. Specifications of research model using simultaneous equations and allegedly with the method Two Stages Least Squares (2SLS). The data used is secondary data with the time span from 1981 to 2014. The results showed that a decrease in the retail price of rice is able to reduce poverty. But the effect is relatively small. Real retail rice price increase 1 percent would increase poverty by 0.037 percent in the short term and amounted to 0.124 percent in the long term. Economic growth to be the only variable that significantly affect poverty. Increase economic growth by 1 percent would reduce poverty by 0.090 percent in the short term and amounted to 0.306 percent in the long term. In an effort to reduce the number of poor people, government purchasing price policy should be followed by other rice policy, such a policy increase the area of irrigated area.